The Relationship Between Organizational Culture and Administrative Management Performance in the Public Service Sector in Labuhanbatu Regency - Fikriah, Anni Zhofaul; Situmorang, Hotmauli; Sary, Irma; Ritonga, Sahrona; Harahap, Amin (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze the relationship between organizational culture and administrative management performance in the public service sector of Labuhanbatu Regency. Using a quantitative correlational approach, data were collected through structured questionnaires from 120 civil servants across various local government agencies. The analysis revealed a significant positive relationship between organizational culture and administrative performance (r = 0.643, p < 0.01). Clan and Market culture types emerged as the most influential predictors, while Adhocracy and Hierarchy cultures showed no statistical significance in the regression model. These findings highlight the importance of fostering collaborative and result-oriented work cultures to support sustainable bureaucratic reform.